Quality of life of patients one month after open heart surgery according to the SF-36 health scale - Trung, Nguyen Thanh; An, Le Van; Thang, Doan Chi; Victoria, Ton-Nu (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Introduction: Quality of life after open heart surgery shows the level of impact on the patients; moreover, it also reflects physical, functional, and psychosocial decline caused by diseases of the entity. This study evaluates the characteristics of quality of life of patients one month after open heart surgery according to the SF-36 health scale at Hue Central Hospital. Methods: This was a cross - sectional descriptive study of 217 patients who underwent open heart surgery at the Cardiovascular Center, Hue Central Hospital, from August 1, 2022, to April 30, 2023. Results: The mean general quality of life score was 64.21 ± 15.71, and the mean physical and mental component summary scores were 69.44 ± 16.08 and 58.98 ± 15.74, respectively. The average of eight health domains scores was physical functioning (84.42 ± 12.21); role physical (86.17 ± 22.41); bodily pain (46.77 ± 20.47); general health (60.38 ± 14.17); vitality (62.05 ± 27.01); role emotional (58.54 ± 11.27); mental health (64.22 ± 12.74); social functioning (51.09 ± 14.51). The mean anxiety disorder and perceived level of social support scores were 9.28 and 65.14, respectively. Conclusion: The quality of life of patients after open heart surgery is quite good, anxiety disorders and perceived levels of social support are high.